Penggunaan Media Alat Peraga sebagai Upaya untuk Meningkatkan Minat dan Hasil Belajar Siswa pada Mata Pelajaran IPA - Erike Octavia Yolanda; Setyaningsih Wulandari (Sekolah Tinggi Agama Islam YPBWI Surabaya, 2023)
Education is an effort to prepare students to face the future and changes in society that are so rapid, especially science and technology. Science is referred to as a science that studies events that occur in nature. The research objective was to determine student learning outcomes using the circulatory system visual aids. The research method is quasi experimental research. The findings are that the response to media teaching aids on the circulatory system material in humans is classified as very good category, students are interested and have enthusiasm in the learning process, the average pretest learning outcomes are 53.6 and the posttest learning outcomes 89.1. The argument is that renewal of the source of teaching materials or teaching aids used in the learning process is an innovation to perfect or improve learning outcomes so that the material presented becomes interesting and fun by using awareness system props blood in science learning.Keyword: teaching aid media, blood circulation system